2020
DOI: 10.33134/njmr.248
|View full text |Cite
|
Sign up to set email alerts
|

Access to Social Capital and Educational Returns for Children of Immigrants: Evidence from Three Swedish Studies

Abstract: In this article, we study whether social capital contributes to ethnic inequality in education or whether there is evidence of counter-stratification. We use data from three surveys of Swedish ninth-graders in different contexts to fit regression models for access to social capital and educational returns. Our results show that students with parents from Asia or Southeast Europe had equal or better access to social capital, compared to children with at least one parent born in Sweden. Results for children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
1
7
1
Order By: Relevance
“…This indicates that current status is less important for access to social capital than past status. Like previous research (Nygård & Behtoui, 2020), the results showed a substantial positive association between family contacts and having two foreign-born parents. However, the magnitude of this association was substantially lower (0.16 as opposed to 0.30 for two foreign-born parents) when controlling for parents' Table 2.…”
Section: The Relationship Between Pre-migration Status and Social Capsupporting
confidence: 84%
See 2 more Smart Citations
“…This indicates that current status is less important for access to social capital than past status. Like previous research (Nygård & Behtoui, 2020), the results showed a substantial positive association between family contacts and having two foreign-born parents. However, the magnitude of this association was substantially lower (0.16 as opposed to 0.30 for two foreign-born parents) when controlling for parents' Table 2.…”
Section: The Relationship Between Pre-migration Status and Social Capsupporting
confidence: 84%
“…Networks also vary from family to family. Empirical findings are consequently mixed with regard to whether immigrant families have more or less resource-rich social networks than non-immigrant families (for overview, see Nygård & Behtoui, 2020). This further suggests that the association between ethnicity and network resources is neither simple nor straightforward.…”
Section: Immigrant Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in other countries found higher levels of social capital among majority members (Behtoui, 2007 ; Li et al, 2008 ; McDonald, 2011 ). However, a recent study looking at students’ social capital did not observe a consistent capital deficit for minorities either (Nygård & Behtoui, 2020 ). Perhaps differences in access to social capital develop later in life, potentially due to minorities’ lower career success and segregated personal lives, and are less apparent in young people’s social capital.…”
Section: Discussionmentioning
confidence: 95%
“…This translates into high expectations among parents, and high aspirations among their children. Young people with an immigrant background are also sometimes supported by a more resource-rich contact network than their families' current class position would suggest (for overview, see Nygård & Behtoui 2020). They therefore tend to exhibit high levels of educational and career aspirations, even when studying in disadvantaged schools (Nygård 2017;Feliciano & Lanuza 2018).…”
Section: Theorymentioning
confidence: 99%